The ground spider genera Leptodrassex Murphy, 2007 and Leptopilos Levy, 2009 (Araneae: Gnaphosidae) in southern Africa, including the description of a new genus and seven new species - Haddad, Charles R.; Booysen, Ruan (Magnolia Press, 2022)
The ground spider genera Leptodrassex Murphy, 2007 and Leptopilos Levy, 2009 are recorded from southern Africa for the first time, with the description of five new species: Leptodrassex murphyi sp. nov. (♂ ♀) from Mozambique and South Africa, and L. capensis sp. nov. (♀) from South Africa; Leptopilos butleri sp. nov. (♂ ♀) and L. vasivulva sp. nov. (♂ ♀) from Botswana, South Africa and Zimbabwe, and L. digitus sp. nov. (♂ ♀) from South Africa. Further, the new genus Afrodrassex gen. nov. is described, with the type species A. balrog sp. nov. (♂ ♀) from South Africa and Angola, and A. catharinae sp. nov. (♂ ♀) from South Africa described therein. Details of the somatic and genitalic morphology of all three genera are examined by scanning electron microscopy, and revised descriptions of Leptodrassex and Leptopilos are presented.
Keywords: Afrotropical; Angola; Botswana; Endemic; Leptodrassinae; Mozambique; South Africa; Zimbabwe